‘Friendship’ in the Tradition of Islamic Political Philosophy - Morteza Bahrani; Seyed Mohsen Alavipour (حکمت معاصر, 2017)
In the wake of the Greek classic philosophers, ‘friendship’ as a philosophical and political concept has also been considered in the political philosophy of Muslim thinkers. However, they considered this category differently due to the differences between Islamic thought and Greek thought in thier totality. Downplaying the importance of this concept in the context of political thinking and taking advantage of some auxiliary concepts, Islamic philosophers sought to put aside the concept in their political philosophy. Examining the concept of friendship in the opinions of philosophers such as Kennedy, Farabi, Ameri and Nasir al-Din al-Tusi through a content analysis of their works, this paper shows that Muslim scholars in borrowing ideas from Greek philosophers, represented a special narrative of the constitutive concepts of political system, based on their intellectual contexts, which in some cases is in contradiction with the approach of the Greek philosophers.